1997
DOI: 10.5860/crl.58.6.509
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Online Menus: A Quantitative Experiment

Abstract: A uniform interface to multiple, varied databases enhances searching and reduces the need for end-user training. The uniformity, however, can make it more difficult to select appropriate resources. This article describes a quantitative study at the University of Washington Libraries that examined the effect of terminology and screen layout on students’ ability to correctly select databases from an introductory screen, the Session Manager. Results indicate a significant improvement in students’ ability to navig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Empirical methods, particularly a formal usability test, have been more frequently used than inspection methods in digital libraries. In 1997, Eliasen et al (1997) tested users' abilities to select relevant databases from a library homepage. Participants were asked to perform tasks using three versions of low‐fidelity prototypes, and the researchers compared the prototypes on the basis of the user observations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical methods, particularly a formal usability test, have been more frequently used than inspection methods in digital libraries. In 1997, Eliasen et al (1997) tested users' abilities to select relevant databases from a library homepage. Participants were asked to perform tasks using three versions of low‐fidelity prototypes, and the researchers compared the prototypes on the basis of the user observations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study found that student search success increased as a result of enhancements to the database interface. 4 However, the interface discussed in this article was not Web based. In an article that examined and compared the GUIs of several online database services, Allison J.…”
Section: Review Of the Literaturementioning
confidence: 99%